1987
DOI: 10.1007/bf02554289
|View full text |Cite
|
Sign up to set email alerts
|

A concept of the anatomy of the anal sphincter mechanism and the physiology of defecation

Abstract: A review of the new concepts of the anatomy of the anal sphincter mechanism and the physiology of defecation is presented. The external sphincter is a triple-loop system; each loop can function as a separate sphincter through voluntary inhibition action and mechanical compression. Stress defecation resulting from internal sphincter damage is described. A new technique for repair of rectal incontinence is presented, which depends on inducing continence not only by mechanical compression, but also by voluntary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
7

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 15 publications
2
51
0
7
Order By: Relevance
“…Just inside the anus is the external anal sphincter (EAS) complex, described by Sha®k as three counterpoised U-shaped loops (Figure 1). 10 The upper loop, formed mainly by puborectalis, arises from the symphisis pubis, loops around the upper part of the rectal neck and opens ventrally. It is innervated by the inferior haemorrhoidal nerve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just inside the anus is the external anal sphincter (EAS) complex, described by Sha®k as three counterpoised U-shaped loops (Figure 1). 10 The upper loop, formed mainly by puborectalis, arises from the symphisis pubis, loops around the upper part of the rectal neck and opens ventrally. It is innervated by the inferior haemorrhoidal nerve.…”
Section: Introductionmentioning
confidence: 99%
“…It is supplied by the inferior haemorrhoidal nerve. 10,11 As each loop has its own separate bilateral nerve supply, each can function as a sphincter independently.…”
Section: Introductionmentioning
confidence: 99%
“…They function to oppose, inter rupt or terminate the act of evacuation. 6,7 The levator ani muscle is a funnel with a transverse part called the levator plate and a vertical part called the suspensory slingS (Fig 1). It is a vesical and rectal neck dilator, whereas the puborectalis is a neck constric tor.…”
Section: Physioanatomical Considerationsmentioning
confidence: 99%
“…Oh et al (1972) reported that the EAS comprised of two compartments, superficial and deep compartments, each of the compartments composed of two layers of sphincter muscles. Shafik (1975) popularized the triple-loop system of the EAS. Regarding the levator ani, it is generally accepted that this muscle is divided into three distinct muscles, the puborectalis, pubococcygeus, and iliococcygeus.…”
mentioning
confidence: 99%